Predictors of Five Days Mortality in Diabetic Ketoacidosis Patients: a Prospective Cohort Study - Suhendro Suwarto; Bambang Sutrisna; Sarwono Waspadji; Herdiman T Pohan (Acta Medica Indonesiana)
Aim: to determine the role of serum lactate and diabetic ketoacidosis (DKA) severity as predictors for five-days mortality in DKA patients. Methods: a prospective cohort study was conducted in DKA patients admitted to emergency department (ED) at Cipto Mangunkusumo Hospital, Jakarta, Indonesia, during 2007-2008 periods. Predictors for 5 days mortality in DKA patients in this study including serum lactate and DKA severity (plasma glucose, arterial blood pH, serum bicarbonate, osmolality, anion gap, and alteration in sensorium) at admission. Cox’s Proportional Hazard Regression Analysis was used to determine independent predictors for 5-days mortality among study population. Results: sixty patients with diabetic ketoacidosis were enrolled in the study; in which 24 (40%) patients were died within 5 days after admission. In the multivariate analysis, the lactate level ≥4 mmol/L (HR, 3.09; 95% CI, 1.36-7.05) and altered in sensorium stuporous/comatose (HR, 3.38; 95% CI, 1.45-7.87) were identified as independent predictors for 5-days mortality in DKA adult patients. Conclusion: lactate level ≥4 mmol/L and altered in sensorium stuporous/comatose can be used to predict 5-days mortality in adult patients with DKA.